High-efficiency chiral meta-lens - Benedikt Groever (Nature Portfolio, 2018)
Abstract We present here a compact metasurface lens element that enables simultaneous and spatially separated imaging of light of opposite circular polarization states. The design overcomes a limitation of previous chiral lenses reliant on the traditional geometric phase approach by allowing for independent focusing of both circular polarizations without a 50% efficiency trade-off. We demonstrate circular polarization-dependent imaging at visible wavelengths with polarization contrast greater than 20dB and efficiencies as high as 70%.